Advanced transceiver design for high-rate wireless communication systems - A S Madhukumar (2010)
Over the recent years, the world has seen prolific growth in the Internet. There has been tremendous growth in the number of users having access to Internet and there is still no sign of slowing down. New trends of application has emerged and from what was once dominated by text-rich content, new applications promise to take users’ experience to a higher level through multimedia streaming and virtual reality images. With such tremendous growth, Internet has brought lots of convenience to us and it is rapidly becoming a vital part of our lives, instead of just luxurious experience for some. Today’s wireless systems are mainly capable of supporting limited mobility and merely serve as replacement for wires. However, most wireless systems available today performs poorly under high mobility conditions. Next generation mobile communication systems face enormous challenge and rigorous research activities are currently going on. In order to meet those challenges stated above, future mobile communication systems need to revolve from the current systems in order for it to be able to compete with fixed-line